Mentality and National Character as Semiotic Regulators of Communicative Behavior - Korolyov, Igor; Domylivska, Liudmyla (Journal of History Culture and Art Research, 2020)
The article proposes the consideration of the concepts of mentality and national character from the perspective of cognitive semiotics, which are semiotic regulators of the process of communication between representatives of different linguistic cultures, in particular, national communicative behavior. Special attention is paid to highlighting the symbolic status of traditions, etiquette and ritual norms, stereotypes, ready-made thoughts, schemes for explaining phenomena and events, causal attribution mechanisms in the communicative consciousness of a national linguistic personality, which form the cognitive-semiotic component of the mentality and national character of representatives certain linguistic culture. The theme of the thesis is that national communicative behavior reflects centuries-old traditions of a particular ethnos, manifested in linguistic and cultural competence, as well as etiquette and ritual norms caused by knowledge and stereotypical representations of the cognitive base of interactants. The observance of traditions and etiquette and ritual norms in national communicative behavior causes the formation of national values of communication participants as representatives of a certain linguaculture, reflecting the cognitive-semiotic specificity of the mentality and national character of the individual people as main regulators of the communication process. As a result of the proposed cognitive-semiotic approach to the analysis of national communicative behavior, the opinion is expressed that in typical invariant monocultural and intercultural situations of communication, each interactant resorts to the formed and fixed in the own consciousness system of semiotypes for organizing the perception and decoding of information, providing it with some assessment and interpretation.